ANALYSIS OF POTENTIAL SUSTAINABLE SHRIMP JERBUNG (Fenneropeneus merguinsis) LANDED AT FISH AUCTION PLACE PANGANDARAN WEST JAVA USING SCHAEFER AND WALTER HILBORN METHOD - Syarof, Zaka; Suryanti, Ani (Jurnal Perikanan Unram, 2025)
TPI Pangandaran is a fishing base with the highest fish landing productivity in Pangandaran Regency, one of the commodities landed is jerbung shrimp (Fenneropenaeus merguiensis). High demand for jerbung shrimp leads to increased fishing intensity, so an analysis of sustainable potential is needed to maintain the sustainability of jerbung shrimp. Analysis of sustainable potential with the Maximum Sustainable Yeield (MSY) approach is important to maintain the sustainability of shrimp resources. The purpose of this study was to analyze the value of CPUE, FPI, and MSY of jerbung shrimp. The method used to analyze the value of MSY is the surplus production method with the approach of Walter Hilborn and Schaefer. The results showed that the CPUE value fluctuated during 2017-2022, with the highest value of 88.67 kg/trip in 2018 and the lowest value of 23.44 kg/trip in 2022. The standard fishing gear with the highest value of FPI is Trammel net. The MSY value using the Schaefer method is 917,990.50 with a Total Allowable Catch (TAC) of 734,392.4 , while the Walter Hilborn method produces an MSY value of 418,065.50 with a TAC of 334,452.4 ,. The exploitation of jerbung shrimp in TPI Pangandaran is still a safe condition. The R square value with Walter Hilborn method is greater than the Schaefer method, which is 0.90254. The value of R square which is greater or close to 1 indicates that in this study the Walter Hilborn method is more relevant to determine MSY and TAC of jerbung shrimp